2003
DOI: 10.1659/0276-4741(2003)023[0156:eomogl]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Manure on Grazing Lands in Ethiopia, East African Highlands

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Livestock stocking management is less straightforward, however. While the determination of livestock density varies by environment and livestock type, Taddesse et al (2003) reported that medium-stocking intensity can lead to higher species richness compared with both a high-stocking intensity and the non-grazed control, as well as resulting in less soil compaction than the high-stocking intensity treatment. These results may not hold in other situations because of the diverse conditions found in smallholder livestock keeping systems.…”
Section: Soil Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Livestock stocking management is less straightforward, however. While the determination of livestock density varies by environment and livestock type, Taddesse et al (2003) reported that medium-stocking intensity can lead to higher species richness compared with both a high-stocking intensity and the non-grazed control, as well as resulting in less soil compaction than the high-stocking intensity treatment. These results may not hold in other situations because of the diverse conditions found in smallholder livestock keeping systems.…”
Section: Soil Managementmentioning
confidence: 99%
“…For example, Srinivasarao et al (2012) showed a positive interaction between the application of manure and mineral fertilizer on carbon stocks in the soil in semiarid regions of India, with beneficial effects on crop yield stability. Taddesse et al (2003) demonstrated positive impacts of manure application in the Ethiopian highlands on pasture biomass production, species richness and water infiltration rates. The GHG emissions dimension associated with manure is complex.…”
Section: Manure Managementmentioning
confidence: 99%
“…Effective restoration practices should be based on local perceptions of soil erosion and should include easily available management options (Kiome & Stocking, 1995). The application of manure has demonstrated to positively affect the infiltration capacity of soils and plant production on grazed lands (Tadesse et al, 2003) at low cost. In addition, mulching can both enhance conditions for plant growth in harsh environments (Blanco-García & Lindig-Cisneros, 2005) and protect topsoil against erosion (Roose & Barethès, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…But, how variations in the climate influence cattle depend on the ecological setting, and how variations in cattle influence the population, depend on the availability of alternative energy sources as well as the cultural setting. The role of cattle in developing countries is as a source of high-quality food, as draft animals, and as a source of manure and fuel (Scoones, 1992; Taddesse et al, 2003). Cattle represent important contribution to household incomes (Seo & Mendelsohn, 2006), and in drought prone areas they can act as an insurance against weather risk (Fafchamps & Gavian, 1997).…”
Section: Introductionmentioning
confidence: 99%